1971
DOI: 10.1002/kin.550030204
|View full text |Cite
|
Sign up to set email alerts
|

Rotating sector study of the gas phase photolysis of the carbon tetrachloride–cyclohexane system

Abstract: The rate constant for the combination of trichloromethyl radicals in the gas phase has been measured by applying the rotating sector technique to the gas phase carbon tetrachloride-cyclohexane photochemical system. A temperature-independent rate constant, ks, of 3.9 f 1.0 X lo'* cc mole-' sec-' was found. Arrhenius parameters for the reaction cc1, $-c -CsH12 5 CHCL f c -C6Hll were found to be given by the expression log k4 = 11.79 -(10,700/2.3 R T )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

1971
1971
1976
1976

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 6 publications
4
8
0
Order By: Relevance
“…However, a puzzling aspect with respect to these data is that the rate constants are not affected by the nature of the solvent nor, at least in the case of the di-tertiary butyl peroxide solution, by temperature variation. I t is difficult to reconcile these findings, which imply a lack of constraint of the liquid medium on the kinetics of biradical reactions, with the observation that the rate constant in solution was found to be lower by a factor of approximately 50 than that determined in the gas phase, where temperature-independent 2k4 values of 3.9 X 10l2, 4.6 X 10l2, and 7.9 X 10l2 cm3/mole.sec were obtained [14,20,21]. The only experimental evidence which also seems to cast some doubt on the validity of the 2k4 'V 1 X 10" cm3/mole.sec value stems from a recent study of Griller and Ingold [22].…”
Section: Kinetic Scheme and Mechanismmentioning
confidence: 69%
See 2 more Smart Citations
“…However, a puzzling aspect with respect to these data is that the rate constants are not affected by the nature of the solvent nor, at least in the case of the di-tertiary butyl peroxide solution, by temperature variation. I t is difficult to reconcile these findings, which imply a lack of constraint of the liquid medium on the kinetics of biradical reactions, with the observation that the rate constant in solution was found to be lower by a factor of approximately 50 than that determined in the gas phase, where temperature-independent 2k4 values of 3.9 X 10l2, 4.6 X 10l2, and 7.9 X 10l2 cm3/mole.sec were obtained [14,20,21]. The only experimental evidence which also seems to cast some doubt on the validity of the 2k4 'V 1 X 10" cm3/mole.sec value stems from a recent study of Griller and Ingold [22].…”
Section: Kinetic Scheme and Mechanismmentioning
confidence: 69%
“…The kinetics of the latter reaction in the liquid phase have been studied by several methods [ll-131, and there is good agreement between the different determinations. In addition, the gas-phase kinetics of H atom abstraction from cyclohexane relative to that of cc13 combination have recently been investigated by White and Kuntz [14] and Tedder and coworkers [ 151, and the rate expressions derived by both groups are also in good agreement. Thus the supplementary results of this study could make it possible to examine the effect of the phase on the activation parameters of a radical metathesis reaction.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…4. Kuntz et al found that the gas phase Arrhenius parameters for hydrogen abstraction from cyclohexane by cc13 [19] and CF3CC12 [20] are very close. The A factors are practically equal while the activation energy for the abstraction of hydrogen by CF3CC12 is lower by 1 kcal/mole than that for the cc13 radical.…”
Section: Estimation Of the Arrhenius Parameters Of Reaction (3u)mentioning
confidence: 95%
“…The absolute rate constant for the combination of trichloromethyl radicals as measured from the photochemical systems (CC13H + Clz 4-hv) [ I ] and (CC1, 4-c-C6H12 + hv) [2] give values in excellent agreement: log k = 1266 and log k = 12.59, respectively. Since data are now available for the absolute rate constant for the combination of 2,2-dichloro-l,l, 1-trifluoroethyl radicals as measured from the photochemical system (CF3CC13 4-c-C6H12 + hv) [3], it seemed of interest to test the feasibility of determining this constant from the photochemical system (CF3CClzH + CIZ + hv).…”
Section: Introductionmentioning
confidence: 95%